2021
DOI: 10.1080/13880209.2021.1903046
|View full text |Cite
|
Sign up to set email alerts
|

Pomelo peel oil suppresses TNF-α-induced necroptosis and cerebral ischaemia–reperfusion injury in a rat model of cardiac arrest

Abstract: Context Pomelo peel oil (PPO) [ Citrus maxima (Burm.) Merr. (Rutaceae)] is reported to possess antioxidant and antimelanogenic activities. Objective To investigate the effect of PPO [ Citrus maxima (Burm.) Merr. cv. Shatian Yu ] on tumour necrosis factor-α (TNF-α)-induced necroptosis in cerebral ischaemia–reperfusion injury (CIRI) after cardiac arrest (CA). Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We used NDS to identify the protective effect of PPEO and determine the efficacy and safety dose at 50 mg/kg. In fact, different dose of PPEO was adopted due to different research aim in our other studies in the same period [ 6 , 7 ]. Nissl staining and electron microscopy were used to observe the protective effect of PPEO from general to ultrastructural level, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used NDS to identify the protective effect of PPEO and determine the efficacy and safety dose at 50 mg/kg. In fact, different dose of PPEO was adopted due to different research aim in our other studies in the same period [ 6 , 7 ]. Nissl staining and electron microscopy were used to observe the protective effect of PPEO from general to ultrastructural level, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies report that citrus and its products have good antioxidant properties because of its high content of active substances such as terpenes, aldehydes, esters, and ketones [ 5 ]. PPEO, a crude compound extracted from pomelo peel, is considered to have potential therapeutic effects for its antioxidant properties or other biological activities [ 6 , 7 ]. In this study, we selected Shatian pomelo peculiar belonging to Rongxian, Guangxi, and extracted the essential oil from outer peel by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…CA also triggers a sepsis-like inflammatory response with expression of TNFα up-regulated in cerebral ischemia. Systemic selective anti-TNFα therapies improved early recovery from CA, in both small and large animal models (4,5). Our prior studies in multiple models of CA in rats, identified a unique early cytokine response specifically in striatum, showing a dramatic >100-fold increase of TNFα vs. other brain regions including hippocampus, where no increase in TNFα was seen (6)(7)(8).…”
Section: Introductionmentioning
confidence: 91%
“…While early ischemic brain injury is the result of energy failure, neuro-inflammation could contribute, or even represent a major cause of delayed neuronal death. Tumor necrosis factor alpha (TNFα) is a pivotal cytokine that can induce neuronal apoptosis and/or necroptosis, and increase neuroinflammation (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…In a 7-minute ventricular fibrillation rat model of CA, Wang et al [ 99 ] showed that IV infusion of pomelo peel oil at doses 10, 20, and 40 mg/kg within 10 minutes post-ROSC increased NDS and enhanced survival. This was associated with a reduction of histological brain injury and the attenuation of necroptosis marker (TNF-α, RIPK1 [receptor-interacting serine/threonine-protein kinase 1], RIPK3 [receptor-interacting serine/threonine-protein kinase 3], p-MLKL/MLKL [phosphorylated mixed lineage kinase domain-like protein/mixed lineage kinase domain-like protein]) expression.…”
Section: Neuroprotective Approaches In Ca-induced Brain Injurymentioning
confidence: 99%